Adolescents' participation in their healthcare: A sociomaterial investigation of a diabetes app. (April 2019) - Ledderer, Loni; Møller, Anne; Fage-Butler, Antoinette
Objective: This article explores how a diabetes app called Diapplo affected adolescents' participation in their healthcare by investigating adolescents' meaning-making in relation to their use of the app. Methods: Using a qualitative single case-study design, we adopted a multimethod responsive approach to data generation that included written data from the app development process, individual and group interviews and observations of the adolescents in the clinical situation. This article presents the results from a qualitative content analysis of group and individual semi-structured interviews conducted with five adolescents diagnosed with type 1 diabetes during and after the four-week test phase of a prototype of the app. Results: The adolescents appreciated the diabetes app's design and interface and having an overview of their blood glucose values. However, they stated that the app's content only partly met their needs and they considered several of its features unnecessary. They would have liked the app to have a social platform and emphasized that the app should be compatible with their blood glucose monitors and pumps for them to continue using it. Conclusions: The participants in our study highlighted the value of social platforms integrated in health apps for patient participation, as well as their preference for health app features that reduced the effort of managing their chronic condition and facilitate greater knowledge. Theories of sociomateriality and material participation helped to account for the challenges of integrating users' perspectives, suggesting the value of early, comprehensive identification and prioritization of users' values when developing mobile health technologies.